Expert Validation: Development of an Ethnoscience-Based E-Module to Improve Students' Critical Thinking Skills and Environmental Awareness - Yovita, Yovita; Pizaini, Pizaini; Berlian, Mery; Tahir, Musa; Vebrianto, Rian (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop an ethnoscience-based e-module on the subject of Living Things and Their Environment to improve critical thinking skills and environmental awareness of junior high school students. The background of this study is based on the weaknesses of conventional learning which is still teacher-centered, abstract, and does not integrate local cultural values thus hampering active student involvement and their understanding of environmental issues. The study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects were junior high school students in Pekanbaru City. The instruments used included a validity questionnaire from media & technology experts, material & pedagogical experts, linguists, and ethnoscience experts; as well as a questionnaire on teacher practicality and student practicality. The results of validation by media, language, material, and ethnoscience experts showed that the e-module had a very good validity level with an average of 88.25%, as well as a very good practicality value with an average of 85%. Thus, this ethnoscience- based e-module is declared feasible, practical, and effective as a contextual learning medium that integrates scientific concepts with local wisdom and supports 21st-century learning